The Prognostic Significance of the DBIL/HDLC Ratio in Patients With Dilated Cardiomyopathy - Xinyi Wang; Qiqi Song; Qingqing Zhang; Xinyi Li; Jiaqi Wang; Jiantao Gong; Ziyi Zhang; Ning Tan; Suk-Ying Tsang; Wing-tak Wong; Dunliang Ma; Lei Jiang (Cardiovascular Therapeutics)
Conclusion: The DBIL/HDLC ratio could serve as a simple and cost-effective tool for evaluating prognosis in DCM.